Organizing the invisible: Strategies of informal garment workers in Mumbai - Tandiwe Gross; Amar Kharate (International Labour Organization (ILO), 2017)
Dharavi in the heart of Mumbai is home to an estimated 1 million people and of the biggest slum economies in the world. With 86% of India's total workforce working in the informal sector, this papers sheds light on the working and living conditions of a section of this invisible workforce as well as their collective struggles and organizing strategies for a more decent life. The empirical findings suggest that despite massive barriers to organising, informal garment workers develop innovative strategies to gain victories both vis-à-vis employers and the state by organising collectively. The entry point are workers' identities as women and citizens and their struggles around domestic violence, harassment housing and public services. For many workers the trade union membership card gains importance as the first written proof of identity and the support of the collective serves as a protection against violence at home and in the community. In the absence of legal protection, this paper finds that trade union organizing is indispensable for combating rights violations and building bargaining power for increasing income. It also shows that social protection schemes, where they cover informal garment workers, are only effective if workers organize collectively and pressure the state for effective access. The paper shows how trade unions as collective organizations of informal economy workers can be key agents to support the effective delivery of state services and contribute to the transitioning of workers from informal to more protected employment.
Keywords: 330